Form and function of the mantle edge in Protobranchia (Mollusca: Bivalvia) - Salas-Casanova, María del Carmen; Bueno-Pérez, Juan de Dios; López-Téllez, Juan Félix; Checa, Antonio (Elsevier, 2022)
We analyzed, by optical and transmission electron microscopy, the morphology and function of the mantle edge, including the formation of the periostracum, of ten species of protobranchs. Five species from the order Nuculida, four species from the order Nuculanida and one species from the order Solemyida were studied. A second outer fold, which seems to function as a template for the internal marginal crenulations of the valves, is present in the crenulated species of Nucula. The minute non-crenulated Ennucula aegeensis shows the glandular basal cells displaced toward the periostracal groove, resembling a minute additional fold between the outer and middle folds. Intense secretion of glycocalyx, together with active uptake of particles, have been observed in the inner epithelium of the middle mantle fold and the whole epithelium of the inner mantle fold in all the studied species. Contrary to the rest of the bivalves, all the protobranchs analyzed have two basal cells involved in the formation of the external nanometric pellicle of the periostracum, a character that would support the monophyly of protobranchs. A three-layered pattern is the general rule for the periostracum in protobranchs, like for other bivalves. The presence of pouches of translucent layer inside the tanned dark layer under periostracal folds is characteristic of the species with a folded periostracum; its function is unclear but could give flexibility to the periostracum. The non-nacreous internal shell layer and the presence of translucent pouches under periostracal folds in Sarepta speciosa resemble those found in nuculanids. However, the free periostracum is rather similar to those of N. hanleyi and E. aegeensis, with a continuous vesicular layer. All the latter supports the inclusion of Sarepta in the order Nuculanida but could indicate either a basal lineage or that the translucent vesicular layer is an adaptive trait.
Keywords: Bivalvos; Sarepta; Acila; Nucula; Nuculana; Lembulus; Solemya; Periostracum; Valve crenulations; Ennucul